Pengaruh Kualitas Produk dan Penetapan Harga Terhadap Keputusan Pembelian Konsumen Pada Produk Pestisida Herbisida Bravoxone di Toko UD. Tani Mandiri Desa Pematang Kerasaan Rejo - Wiclyfe Panjaitan, William; Hutapea, Joan (CV. Publikasi Indonesia, 2022)
Agriculture is currently growing rapidly, given that the people's need for food will increase. In this case, many companies, especially in the agricultural sector, compete to offer their products so that they can win the market. The purpose of this study was to determine the effect of product quality and pricing on purchasing decisions for Bravoxone Herbicide products at UD. Tani Mandiri in Pematang Kerasa Rejo Village. The population used is the farmers in the village of Pematang Kerasa Rejo customers UD. Tani Mandiri who bought Bravoxone Herbicide products which sold 124 people. The sample used in this study was 50 respondents using the Slovin formula. The analysis technique uses validity, reliability, descriptive analysis, correlation coefficient, coefficient of determination, t test, and f test. SPSS software version 25. The results show that together product quality and pricing have a positive and significant impact on purchasing decisions. The result of the coefficient of determination test is 0.781 or 78.1%. This shows that 78.1% of purchasing decisions are influenced by product quality and pricing. While the remaining 21.9% is influenced by other variables.